Analyzing how social protection shapes gendered impacts of climate change - Roy, Shalini; Hirvonen, Kalle; Gilligan, Daniel O.; Tambet, Heleene; Hidrobo, Melissa; Mueller, Valerie; Fall, Cheikh Modou Noreyni; Lavaysse, Christophe; Dionne, Malick; Ahmed, Akhter; Hoddinott, John F.; Bakhtiar, M. Mehrab; et al. (CGIAR System Organization, 2024)
Analytical approach for researchers to conduct mixed-method multi-country assessment of how social protection shapes gendered impacts of climate change.